2003
DOI: 10.1002/jcp.10340
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol‐induced growth inhibition and apoptosis in A549 lung cancer cells is mediated by activation of MEK‐MAPK

Abstract: A vast variety of naturally occurring substances have been shown to protect against experimental carcinogenesis and an increasing amount of evidence suggests that kaempferol may have cancer chemopreventative properties. However, the precise underlying protective mechanisms are poorly understood. To elucidate these mechanisms, we challenged human lung cancer cell line A549 with kaempferol and investigated its effects upon cellular growth and signal transduction pathways. Treatment of A549 cells with kaempferol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(117 citation statements)
references
References 62 publications
11
101
1
4
Order By: Relevance
“…This may be due to the presence of flavonoid compound especially kaempferol which also show high cytotoxicity which isolated from high polar fraction of the methanolic extract, in we study the cytotoxicity of MCF-7,A459 cell lines by isolated compound. Our findings are line line with previous studies (Nguyen et al, 2003). Kaempferol is a polyphenol antioxidant found in fruits and vegetables.…”
Section: Resultssupporting
confidence: 94%
“…This may be due to the presence of flavonoid compound especially kaempferol which also show high cytotoxicity which isolated from high polar fraction of the methanolic extract, in we study the cytotoxicity of MCF-7,A459 cell lines by isolated compound. Our findings are line line with previous studies (Nguyen et al, 2003). Kaempferol is a polyphenol antioxidant found in fruits and vegetables.…”
Section: Resultssupporting
confidence: 94%
“…The inhibitory effect of kaempferol on cell proliferation may be attributed by its antioxidation capacity and cytotoxic action. Furthermore, kaempferol inhibits the activity of several enzymes involved in cell growth and signal transduction pathway including cAMP-phosphodiesterase and tyrosine kinase [18], cdc25 phosphatase [17], DNA topoisomerase II, topoisomerase I catalyzed DNA religation [19], proline-directed protein kinase fatty acid in human prostate carcinoma cells, and myosin light chain kinase [20]. Several studies on kaempferol have been reported including the activation of human estrogen receptors and unique signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It can be isolated from tea, broccoli, witch-hazel, propslis, grapefruit, and other plants (Yoshida et al, 2008). The medicinal properties of kaempferol include antioxidant, anti-inflammatory, and anticancer activities (Kampkötter et al, 2007;Kim et al, 2010;Nguyen et al, 2003). Several studies have shown that intake of foods containing kaempferol is associated with reductions in mortality, the incidence of myocardial infarction, and the incidence of cerebrovascular disease, as well as with a slightly reduced risk of coronary heart disease (Geleijnse et al, 2002;Knekt et al, 2002;Lin et al, 2006).…”
Section: +mentioning
confidence: 99%